Hepatitis B virus genetic heterogeneity and drug resistance among jaundiced patients at Coast General Teaching and Referral Hospital, Mombasa County, Kenya - Kasera, Gordon Ochieng'; Nyamache, Anthony Kebira; Onyango, Omondi Kevin; Maingi, John M. (International Journal of Health Sciences, 2021)
Objectives: Hepatitis B virus (HBV) infection and emergence of drug resistance have remained one of the major public health puzzles. This study determined circulating HBV genotypes and nucleoside analog resistance to provide information in choosing the best therapy. Methods: A cross-sectional study was conducted among jaundiced patients visiting Coast General Teaching and Referral Hospital during the period between February and August 2018. A total of 222 patients were recruited and screened for HBsAg following the ethical procedure. Viral DNA was extracted from positive samples, partial HBV-pol gene amplified, and directly sequenced and analyzed using web-based software prediction to genotypic resistance mutations. Results: Forty-seven (21.2%) of the 222 patients tested positive for HBV. Of the 45 samples successfully sequenced, 12 (26.4%) had drug resistance. Six patients (13.3%) had rtV173L, rtL180M, and rtM204V mutations; five subjects (11.1%) with rtL180M and rtM204V while 1 patient (2.2%) had rtM204V mutations. Therefore, all patients had cross-resistance to lamivudine and entecavir. Phylogenetic analysis revealed that HBV genotype A1 35 (74.5%) was predominant. HBV genotypes A3, B, and C2 each occurred once (0.02%). In addition, existence of new HBV genotypes A3, B, and C2 1 (0.02%) in the country was also detected. Conclusion: Findings suggest that HBV-infected patients should not be put on lamivudine monotherapy. These patients should be on a combination therapy; tenofovir plus lamivudine or emtricitabine to prevent emergence of drug resistance variants. In addition, HBV genotype A1 remains the most predominant genotype in this region. The detected new genotypes variants indicate a possible existence of 0.02% circulation within the population.